2015
DOI: 10.1037/pspi0000001
|View full text |Cite
|
Sign up to set email alerts
|

Actors conform, observers react: The effects of behavioral synchrony on conformity.

Abstract: Engaging in synchronous behavior can induce a more general disposition to copy others, which increases the tendency to conform to others' preferences in an unrelated choice situation. In contrast, observing others perform synchronous behavior can induce psychological reactance and decrease conformity to others' preferences. Five experiments confirmed these different effects and circumscribed the conditions in which they occurred. Actors typically focus their attention on the goal to which their synchronous beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…The finding that increases in group cohesion do not mediate these effects supports the work of Dong et al (2015), Lumsden et al (2014), and Reddish et al (2014). However, it did not support the work of Reddish et al (2013), Wiltermuth and Heath (2009), and Wiltermuth (2012), which found that cohesion partially mediates the relationship between CRM and its social consequences.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that increases in group cohesion do not mediate these effects supports the work of Dong et al (2015), Lumsden et al (2014), and Reddish et al (2014). However, it did not support the work of Reddish et al (2013), Wiltermuth and Heath (2009), and Wiltermuth (2012), which found that cohesion partially mediates the relationship between CRM and its social consequences.…”
Section: Discussionsupporting
confidence: 83%
“…Group cohesion is the feeling of being on the same team and being emotionally connected with other group members. Wiltermuth and Heath (2009), Wiltermuth (2012) found that levels of post-task group cohesion were related to the social effects of coordination, though others (e.g., Reddish et al, 2013; Lumsden et al, 2014; Dong et al, 2015) found no such relationship. The discrepancy in results may be, at least, partially explained by differences in how group cohesion was conceptualized and measured.…”
Section: Direct Vs Indirect Effect (D+ Vs D−)mentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency towards entraining to another person’s movements provides a form of ‘social glue’ that enables groups to work together more effectively. People who move together in time, are more likely to remember [25,26] and like each other [27,28], experience feelings of togetherness and similarity [29], cooperate more effectively [30] and are more likely to conform to each other's behavior [31]. …”
Section: Introductionmentioning
confidence: 99%
“…However, this is not the only starting point for such theorizing. Coming at the problem of cooperation from the perspective of prior work on postural mirroring (LaFrance, 1985), LaFrance (1990) offered a brief theoretical sketch that, while lacking ultimate explanations or phylogenetic accounts, nevertheless directly parallels Hagen et al's perspective on the informational value of synchrony in communicating cohesiveness to both in-group and out-group individuals.Although Hagen and Bryant's signaling paper has been highly cited in work exploring the psychology of synchrony, consonant with McNeill's initial focus, to date, much of this literature has focused not on outwardly signaling coalitional quality in the service of intimidating rivals and attracting allies, but rather on the subjective and behavioral consequences of participation in synchrony, particularly as they pertain to issues of conformity, cohesion, bonding, solidarity, prosociality, and cooperation (see, for example, Wiltermuth & Heath, 2009;Hove & Risen, 2009;Cohen et al, 2010;Kirschner & Tomasello, 2010;Valdesolo et al, 2010;Kokal et al, 2011;Valdesolo & DeSteno, 2011;Wiltermuth, 2012b;Wiltermuth, 2012a;Fischer et al, 2013;Launay et al, 2013;Reddish et al, 2013a;Reddish et al, 2013b; Kirschner & Ilari, 4 2014;Cirelli et al, 2014a;Cirelli et al, 2014b;Fessler & Holbrook, 2014;Lumsden et al, 2014;Sullivan et al, 2014;Dong et al, 2015;Rabinowitch & Knafo-Noam, 2015;Sullivan et al, 2015;Tarr et al, 2015;Zimmermann & Richardson, 2015; Tarr et al, in press; see also Weinstein et al, 2016). In contrast, the question of the interpretation of signals by non-participants has received less attention in this body of work (see Dong et al, 2015, as well as Lumsden et al, 2012, for exceptions).…”
mentioning
confidence: 99%